Manuele Crisolora a Costantinopoli: Con tavole I-XIV - Acerbi, Fabio ca. 20./21. Jh. (Byzantinische Zeitschrift, 2021)
The identification of a "new" handwriting of Manuel Chrysoloras allows to assign to him a number of hitherto unpublished witnesses, all preceding his teaching activity in Florence from 1397. This new dossier illustrates Chrysoloras' youth in Constantinople, providing precious and so far unknown information on his family, his father John, his studies in the anti-Palamite milieux with Isaac Argyros and Demetrios Kydones, and, of course, his books, his graphic education, and his readings. Among these, a special place is occupied by Aristotle's logic: particular attention is therefore paid to a mock-up of a manuscript containing Aristotle’s Organon with a marginal commentary, here attributed to Chrysoloras and realized in a well-known manuscript by his master Argyros.